International study to evaluate PCR methods for detection of Trypanosoma cruzi DNA in blood samples from Chagas disease patients - Schijman, Alejandro G. (2011)
Instituto de Investigaciones en Ingeniería Genética y Biología Molecular (INGEBI-CONICET). Laboratorio de Biología Molecular de la Enfermedad de Chagas (LabMECh). Buenos Aires, Argentina.